Pemanfaatan Dukungan Pengembangan Bisnis Universitas: Faktor Psikologis yang Mendorong Niat Kewirausahaan Mahasiswa: Studi Kasus pada Mahasiswa - R Yovie Ardianto; Aulia Vidya Almadana (Diponegoro Journal of Management, 2025)
The development of entrepreneurship among Generation Z (Gen-Z) students, especially those in higher education, has significantly increased. However, psychological pressure, economic uncertainty, and the challenge of balancing work-life integration often hinder entrepreneurial interest. Universities play a pivotal role in supporting business development for students, but prior studies indicate that institutional support does not always directly enhance entrepreneurial intention. This study aims to examine the effect of university support on Gen-Z students’ entrepreneurial intentions, considering the mediating roles of psychological factors—subjective norms and perceived behavioral control—within the Theory of Planned Behavior (TPB) framework. A quantitative approach using a survey method was employed, with data collected from 422 students at two universities in Semarang, Indonesia. Structural Equation Modeling (SEM) with AMOS was used for analysis. The results indicate that while university support does not have a direct impact on entrepreneurial intention, it significantly influences both subjective norms and perceived behavioral control, which in turn positively affect entrepreneurial intentions. Psychological factors fully mediate the relationship between university support and entrepreneurial intention, emphasizing the importance of incorporating psychological readiness into university entrepreneurship programs.